CRIPTOCOCOSIS Y LINFOCITOPENIA T CD4 IDIOPÁTICA: REPORTE DE UN CASO - Daniel Martin Arsanios (Asociación Colombiana de Infectología, 2021)
Idiopathic CD4 T lymphocytopenia (ICL) is an unusual clinical syndrome characterized by a deficit of circulating CD4 + T cells in the absence of HIV infection or another immunosuppression condition. Patients with this disease may present asymptomatic or with opportunistic infections, the most frequent are cryptococcus, mycobacteria or viral such as herpes zoster. We present a case of a 32-year-old man with no prior disease, in whom retrovirus infection was discarded, with CD4 + T lymphocyte count less than 300 cells/m3 ; ICL was diagnosed after the diagnosis of brain cryptococomas by imaging findings which were consistent with microbiological studies.